INTEGRATIVE SYLLABUS AND MATERIAL MODEL FOR NON-NATIVE SPEAKERS IN AGRICULTURE (MODEL SILABUS INTEGRATIF DAN MATERI AJAR BAHASA INDONESIA BAGI PENUTUR ASING DALAM BIDANG PERTANIAN) - Defina Defina; Yumna Rasyid; Sakura Ridwan; Kalema Christopher; Otaigo Elisha; Mohamedalhabieb Alhafiz Mohamed Alnour (Universitas PGRI Sumatera Barat, 2021)
This study aims to produce a product model of integrative content-based Indonesian teaching syllabus and material in agriculture specifically for level A2 non-native speakers. The method is research and development. Through this initial effort, the syllabus and teaching materials were designed and then validated by experts, followed by revision I, draft II, revision II, design III, effectiveness test, revision III, and final product. The results revealed a high expert validation of draft I, and the effectivity test for db = 7 and α = 0.05 results in ttabel = t(0.05;7)= 1.895, and thit = 14.16235844, leading to acceptance of H1. Based on the research and development results, it can be concluded that the produced syllabus and teaching materials have been effective. This research implies that the syllabus and teaching materials developed can be applied in BIPA IPB and other BIPA with specific objectives in agriculture.